PENGARUH METODE MANHAJI DALAM PEMBELAJARAN BAHASA ARAB (ASPEK MEMBACA) KELAS 2 DINIYAH PONDOK PESANTREN AL MIZAN MUHAMMADIYAH LAMONGAN - Mochamad Ramadhan; Asrori Asrori; Sokhibul Arifin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to determine the influence of the Manhaji method: nahwu Sharaf guidance by reciting in learning Arabic (reading aspect) of the Al Mizan Muhammadiyah Lamongan Islamic Boarding School. The subject of this study is the 2nd grade of Diniyah Islamic Boarding School Al Mizan Muhammadiyah Lamongan. The problem experienced is the factor the factor that students cannot read in Arabic using the Manhaji method. This study uses quantitative research based on the type of data in the from of numbers, namely in the from of numbers through the suspension process based on the results of this study. The Manhaji method has no effect on Arabic language learning (reading aspect) with a t-value of calculation (0.812) < t-table (2.035), then Ho is accepted and Ha is rejected meaning “The Manhaji Method has no significant effect on the Arabic language learning method (reading aspect)”, with a very low level of relationship seen from the correlation test, namely and R value of 0.140. This shows that level of relationship between the independent variable and the bound variable is very low, so it can be see that the existence of the manhaji method does not improve the Arabic language (reading aspect) of grade 2 students of the Al Mizan Muhammadiyah Lamongan Islamic Boarding School.